2013
DOI: 10.3791/51001
|View full text |Cite
|
Sign up to set email alerts
|

Corticospinal Excitability Modulation During Action Observation

Abstract: This study used the transcranial magnetic stimulation/motor evoked potential (TMS/MEP) technique to pinpoint when the automatic tendency to mirror someone else's action becomes anticipatory simulation of a complementary act. TMS was delivered to the left primary motor cortex corresponding to the hand to induce the highest level of MEP activity from the abductor digiti minimi (ADM; the muscle serving little finger abduction) as well as the first dorsal interosseus (FDI; the muscle serving index finger flexion/e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 49 publications
4
15
0
Order By: Relevance
“…A finding in accordance with behavioral (Bertenthal, Longo, & Kosobud, 2006;Liepelt et al, 2010) and neurophysiological (Press, Bird, Walsh, & Heyes, 2008) studies showing motor facilitation effects for transitive as well as intransitive actions . 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 15 Moreover, the present findings extends previous evidence on response preparation in hand muscles (Newman-Norlund, Noordzij, Meulenbroek, & Bekkering, 2007;Ocampo & Kritikos, 2010;Sartori, Cavallo, Bucchioni, & Castiello, 2011b, 2012bSartori, Betti, & Castiello, 2013a, 2013bSartori et al, 2013c) showing a modulation of CS excitability also when the observed action calls for a gesture involving different body parts with respect to the observed ones. In the present study, observers' upper limb muscles were activated while observing a soccer player kicking a ball straight in their direction.…”
Section: Discussionsupporting
confidence: 86%
“…A finding in accordance with behavioral (Bertenthal, Longo, & Kosobud, 2006;Liepelt et al, 2010) and neurophysiological (Press, Bird, Walsh, & Heyes, 2008) studies showing motor facilitation effects for transitive as well as intransitive actions . 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 15 Moreover, the present findings extends previous evidence on response preparation in hand muscles (Newman-Norlund, Noordzij, Meulenbroek, & Bekkering, 2007;Ocampo & Kritikos, 2010;Sartori, Cavallo, Bucchioni, & Castiello, 2011b, 2012bSartori, Betti, & Castiello, 2013a, 2013bSartori et al, 2013c) showing a modulation of CS excitability also when the observed action calls for a gesture involving different body parts with respect to the observed ones. In the present study, observers' upper limb muscles were activated while observing a soccer player kicking a ball straight in their direction.…”
Section: Discussionsupporting
confidence: 86%
“…Particularly for experiment 2, we demonstrated a general significant facilitation of corticospinal excitability during movement observation, i.e. MEPs elicited during grasp observation were larger than during baseline measurements which is in line with previous studies Alaerts, Van Aggelpoel, Swinnen, & Wenderoth, 2009;Fadiga, Fogassi, Pavesi, & Rizzolatti, 1995 Lemon, 2009;Sartori, Betti, & Castiello, 2013). Accordingly, the general MEP facilitation is more pronounced for FDI than for ADM (as found in Exp.…”
Section: General Versus Grip Specific Changes Of Corticomotor Excitabsupporting
confidence: 91%
“…It seems that it is not only the phase or the kinematics of the observed action that modulates the level of motor coding, but an interplay of low‐ and high‐level factors (e.g., the context; Iacoboni et al ., ). In this vein, a modulation of corticospinal excitability violating the classic motor facilitation effect has been shown when participants are instructed to perform incongruent actions (Newman‐Norlund et al ., ; Ocampo & Kritikos, ), when the observed action itself calls for a gesture involving different hand muscles with respect to the observed ones (Sartori et al ., 2013a‐c), and when participants involved in face‐to‐face interactions mutually adjust their movements in time and space in the absence of instructions to either imitate or perform a complementary response (Sacheli et al ., , ). In a recent study, observers' upper and lower limb muscles were both found activated while observing a soccer player kicking a ball straight in their direction (Sartori et al ., ), thus suggesting that motor coding might reflect different processes (providing literal copies of the observed action, predictive and non‐congruent muscular activations) in a non‐mutually exclusive way.…”
Section: Discussionmentioning
confidence: 99%